Scopus Scientific Production 2019-2023 in Non-Institutionalized Peruvian Universities with Organizing Commission - Rojas-Yauri, Golber; Castro-Bedriñana, Jorge; Chirinos-Peinado, Doris; Lagos-Quispe, Thalia (Revista General de Información y Documentación, 2024)
Research is a mandatory and essential university function. The study analyzes the behavior of some bibliometric indicators of Scopus 2019-2023 scientific production of the 19 Non-Institutionalized Peruvian universities with an Organizing Commission. By 2023, 1746 documents were found indexed in Scopus. There is an increase in publications in social, agricultural and biological sciences, engineering, information technology and computing, and environmental sciences. The variety of published documents, the level of publication in English, the H indexes of scientific journals and publication by quartiles, the number of qualified research teachers in the national science and technology system of Peru and the areas of publication are identified. Between 2022-2023, the level of publication in Scopus and the number of qualified teachers has increased significantly in this group of universities; However, the level of publication is far below that of institutionalized universities.
Keywords: Scopus; bibliometrics; scientific production; universities with organizing commission; indexed documents